REVIEW PAPER Defects of coagulation and antiphospholipid antibodies in patients up to 40 years old with acute coronary syndrome - Dębska, Agnieszka (Archives of Medical Science, 2005)
A higher prevalence of acute coronary syndromes (ACS) is observed in young patients up to 40 years old. Many differences between young and older patients are described in literature, according to: cardiac risk factors, symptomatology, clinical course, therapy and prognosis as to health or as to life. Except classical risk factors leading to ACS other cardiac predictors are being searched in the group of younger sick persons. It is worth considering the importance of defects of coagulation, such as: proportions’ disorders of tissue factor, tissue plasminogen activator, Leiden factor, protein C, lipoprotein (a) and mutations of propter genes (the role of the polymorphism in the fibrinogen beta-chain gene, prothrombin gene, thrombopoetin gene). There is also the significant role of antiphospholipid antibodies in the pathogenesis of cardiac ischemic episodes, especially in young patients. These antibodies are determined in 10-20% of cases. However, among classical cardiac risk factors the most common are: smoking, burdening family history and lipid disorders. Often in the group of young patients no atheromatous coronary arteries are angiographically described or changes are not so advanced. It is connected with a smaller necessity of interventional procedures, also surgical, and with a better prognosis – without complications and recurrent ACS.